By Canoe and Speedboat: The Recent Expansion of the Ìlàjẹ Fishing Trade - Kayọde Joseph Onipede (Yoruba Studies Review)
Competition has remained a significant feature of trade, particularly in regions with diverse social groups like the Niger Delta region of Nigeria. This article examines the expansion of trade among the Ìlàjẹ communities of Ondo State in the coastal area of Yorùbáland, which to the best of our knowledge has not been documented. Historical method of data collection and analysis were employed in the study. These include primary and secondary sources. The primary sources are mainly comprised of interviews of key informants and participants’ observations. The secondary sources consist of journal articles and texts. The results were analyzed qualitatively.